Loss of function mutations in GEMIN5 cause a neurodevelopmental disorder. - Kour, Sukhleen; Rajan, Deepa S; Fortuna, Tyler R; Anderson, Eric N; Ward, Caroline; Lee, Youngha; Lee, Sangmoon; Shin, Yong Beom; Chae, Jong-Hee; Choi, Murim; Siquier, Karine; Cantagrel, Vincent; et al. (Nat Commun, 2021)
GEMIN5, an RNA-binding protein is essential for assembly of the survival motor neuron (SMN) protein complex and facilitates the formation of small nuclear ribonucleoproteins (snRNPs), the building blocks of spliceosomes. Here, we have identified 30 affected individuals from 22 unrelated families presenting with developmental delay, hypotonia, and cerebellar ataxia harboring biallelic variants in the GEMIN5 gene. Mutations in GEMIN5 perturb the subcellular distribution, stability, and expression of GEMIN5 protein and its interacting partners in patient iPSC-derived neurons, suggesting a potential loss-of-function mechanism. GEMIN5 mutations result in disruption of snRNP complex assembly formation in patient iPSC neurons. Furthermore, knock down of rigor mortis, the fly homolog of human GEMIN5, leads to developmental defects, motor dysfunction, and a reduced lifespan. Interestingly, we observed that GEMIN5 variants disrupt a distinct set of transcripts and pathways as compared to SMA patient neurons, suggesting different molecular pathomechanisms. These findings collectively provide evidence that pathogenic variants in GEMIN5 perturb physiological functions and result in a neurodevelopmental delay and ataxia syndrome.
Keywords: Alleles; Amino Acid Sequence; Animals; Child, Preschool; Developmental Disabilities; Drosophila; Female; Gene Expression Regulation, Developmental; Gene Knockdown Techniques; Gene Ontology; HEK293 Cells; Humans; Induced Pluripotent Stem Cells; Loss of Function Mutation; Male; Muscle Hypotonia; Myoclonic Cerebellar Dyssynergia; Neurodevelopmental Disorders; Neurons; Pedigree; Polymorphism, Single Nucleotide; Ribonucleoproteins, Small Nuclear; Rigor Mortis; RNA-Seq; SMN Complex Proteins

Mutations disrupting neuritogenesis genes confer risk for cerebral palsy. - Jin, Sheng Chih; Lewis, Sara A; Bakhtiari, Somayeh; Zeng, Xue; Sierant, Michael C; Shetty, Sheetal; Nordlie, Sandra M; Elie, Aureliane; Corbett, Mark A; Norton, Bethany Y; van Eyk, Clare L; Haider, Shozeb; et al. (Nat Genet, 2020)
In addition to commonly associated environmental factors, genomic factors may cause cerebral palsy. We performed whole-exome sequencing of 250 parent-offspring trios, and observed enrichment of damaging de novo mutations in cerebral palsy cases. Eight genes had multiple damaging de novo mutations; of these, two (TUBA1A and CTNNB1) met genome-wide significance. We identified two novel monogenic etiologies, FBXO31 and RHOB, and showed that the RHOB mutation enhances active-state Rho effector binding while the FBXO31 mutation diminishes cyclin D levels. Candidate cerebral palsy risk genes overlapped with neurodevelopmental disorder genes. Network analyses identified enrichment of Rho GTPase, extracellular matrix, focal adhesion and cytoskeleton pathways. Cerebral palsy risk genes in enriched pathways were shown to regulate neuromotor function in a Drosophila reverse genetics screen. We estimate that 14% of cases could be attributed to an excess of damaging de novo or recessive variants. These findings provide evidence for genetically mediated dysregulation of early neuronal connectivity in cerebral palsy.
Keywords: Animals; beta Catenin; Cerebral Palsy; Cyclin D; Cytoskeleton; Drosophila; Exome; Extracellular Matrix; F-Box Proteins; Female; Focal Adhesions; Genetic Predisposition to Disease; Genome, Human; Humans; Male; Mutation; Neurites; rhoB GTP-Binding Protein; Risk Factors; Sequence Analysis, DNA; Signal Transduction; Tubulin; Tumor Suppressor Proteins; Whole Exome Sequencing

Mutations in the mitochondrial ribosomal protein MRPS22 lead to primary ovarian insufficiency. - Chen, Anlu; Tiosano, Dov; Guran, Tulay; Baris, Hagit N; Bayram, Yavuz; Mory, Adi; Shapiro-Kulnane, Laura; Hodges, Craig A; Akdemir, Zeynep C; Turan, Serap; Jhangiani, Shalini N; van den Akker, Focco; et al. (Hum Mol Genet, 2018)
Primary ovarian insufficiency (POI) is characterized by amenorrhea and loss or dysfunction of ovarian follicles prior to the age of 40. POI has been associated with autosomal recessive mutations in genes involving hormonal signaling and folliculogenesis, however, the genetic etiology of POI most often remains unknown. Here we report MRPS22 homozygous missense variants c.404G>A (p.R135Q) and c.605G>A (p.R202H) identified in four females from two independent consanguineous families as a novel genetic cause of POI in adolescents. Both missense mutations identified in MRPS22 are rare, occurred in highly evolutionarily conserved residues, and are predicted to be deleterious to protein function. In contrast to prior reports of mutations in MRPS22 associated with severe mitochondrial disease, the POI phenotype is far less severe. Consistent with this genotype-phenotype correlation, mitochondrial defects in oxidative phosphorylation or rRNA levels were not detected in fibroblasts derived from the POI patients, suggesting a non-bioenergetic or tissue-specific mitochondrial defect. Furthermore, we demonstrate in a Drosophila model that mRpS22 deficiency specifically in somatic cells of the ovary had no effect on fertility, whereas flies with mRpS22 deficiency specifically in germ cells were infertile and agametic, demonstrating a cell autonomous requirement for mRpS22 in germ cell development. These findings collectively identify that MRPS22, a component of the small mitochondrial ribosome subunit, is critical for ovarian development and may therefore provide insight into the pathophysiology and treatment of ovarian dysfunction.
Keywords: Adolescent; Adult; Amenorrhea; Animals; Disease Models, Animal; Drosophila; Drosophila Proteins; Female; Fertility; Homozygote; Humans; Menopause, Premature; Mitochondrial Proteins; Mutation, Missense; Ovarian Follicle; Primary Ovarian Insufficiency; Ribosomal Proteins; Young Adult

Loss of Nardilysin, a Mitochondrial Co-chaperone for α-Ketoglutarate Dehydrogenase, Promotes mTORC1 Activation and Neurodegeneration. - Yoon, Wan Hee; Sandoval, Hector; Nagarkar-Jaiswal, Sonal; Jaiswal, Manish; Yamamoto, Shinya; Haelterman, Nele A; Putluri, Nagireddy; Putluri, Vasanta; Sreekumar, Arun; Tos, Tulay; Aksoy, Ayse; Donti, Taraka; et al. (Neuron, 2017)
We previously identified mutations in Nardilysin (dNrd1) in a forward genetic screen designed to isolate genes whose loss causes neurodegeneration in Drosophila photoreceptor neurons. Here we show that NRD1 is localized to mitochondria, where it recruits mitochondrial chaperones and assists in the folding of α-ketoglutarate dehydrogenase (OGDH), a rate-limiting enzyme in the Krebs cycle. Loss of Nrd1 or Ogdh leads to an increase in α-ketoglutarate, a substrate for OGDH, which in turn leads to mTORC1 activation and a subsequent reduction in autophagy. Inhibition of mTOR activity by rapamycin or partially restoring autophagy delays neurodegeneration in dNrd1 mutant flies. In summary, this study reveals a novel role for NRD1 as a mitochondrial co-chaperone for OGDH and provides a mechanistic link between mitochondrial metabolic dysfunction, mTORC1 signaling, and impaired autophagy in neurodegeneration.
Keywords: Animals; Autophagy; Drosophila; Drosophila melanogaster; Drosophila Proteins; Ketoglutarate Dehydrogenase Complex; Ketoglutaric Acids; Lysine; Mechanistic Target of Rapamycin Complex 1; Metalloendopeptidases; Mitochondria; Molecular Chaperones; Multiprotein Complexes; Neurodegenerative Diseases; TOR Serine-Threonine Kinases

CNV instability associated with DNA replication dynamics: evidence for replicative mechanisms in CNV mutagenesis. - Chen, Lu; Zhou, Weichen; Zhang, Cheng; Lupski, James R; Jin, Li; Zhang, Feng (Hum Mol Genet, 2015)
Copy number variation (CNV) in the human genome is of vital importance to human health and evolution of our species. However, much of the molecular basis of CNV mutagenesis remains to be elucidated. Considering the DNA replication model of 'fork stalling and template switching' for CNV formation, we hypothesized that replication fork progression could be important for CNV mutagenesis. However, molecular assays of replication fork progression at the genome level are technically challenging. Instead, we conducted an estimation of DNA replication dynamics, as the statistic R, using the readily available data of replication timing. Small R-values can reflect 'slowed' replication, which could result from less fork initiation, reduced fork speed or fork barriers. We generated genome-wide profiles of R in the genomes of human, mouse and Drosophila. Intriguingly, the CNV breakpoints in all three genomes showed significantly biased distributions toward the genomic regions with small R-values, suggesting potential replication stress-induced CNV instability. Notably, among the human CNVs with distinct breakpoint junction characteristics, the homology-mediated and VNTR-mediated CNVs contribute the most to the correlation between CNV instability and the statistic R, consistent with the recent findings in the C. elegans and yeast genomes of repeat-induced DNA replication error and consequent CNV formation. The statistic R may reflect both replication stress and the effect of local genome architecture on fork progression. Our concordant observations suggest an important role for DNA replicative mechanisms in CNV mutagenesis and genome instability.
Keywords: Animals; DNA Copy Number Variations; DNA Replication; Drosophila; Genome; Genomic Instability; Humans; Mice

Mutations in KATNB1 cause complex cerebral malformations by disrupting asymmetrically dividing neural progenitors. - Mishra-Gorur, Ketu; Çağlayan, Ahmet Okay; Schaffer, Ashleigh E; Chabu, Chiswili; Henegariu, Octavian; Vonhoff, Fernando; Akgümüş, Gözde Tuğce; Nishimura, Sayoko; Han, Wenqi; Tu, Shu; Baran, Burçin; Gümüş, Hakan; et al. (Neuron, 2014)
Exome sequencing analysis of over 2,000 children with complex malformations of cortical development identified five independent (four homozygous and one compound heterozygous) deleterious mutations in KATNB1, encoding the regulatory subunit of the microtubule-severing enzyme Katanin. Mitotic spindle formation is defective in patient-derived fibroblasts, a consequence of disrupted interactions of mutant KATNB1 with KATNA1, the catalytic subunit of Katanin, and other microtubule-associated proteins. Loss of KATNB1 orthologs in zebrafish (katnb1) and flies (kat80) results in microcephaly, recapitulating the human phenotype. In the developing Drosophila optic lobe, kat80 loss specifically affects the asymmetrically dividing neuroblasts, which display supernumerary centrosomes and spindle abnormalities during mitosis, leading to cell cycle progression delays and reduced cell numbers. Furthermore, kat80 depletion results in dendritic arborization defects in sensory and motor neurons, affecting neural architecture. Taken together, we provide insight into the mechanisms by which KATNB1 mutations cause human cerebral cortical malformations, demonstrating its fundamental role during brain development.
Keywords: Adenosine Triphosphatases; Animals; Brain; Cell Count; Cell Division; Dendrites; Drosophila; Drosophila Proteins; Humans; Katanin; Mice; Microcephaly; Microtubule-Associated Proteins; Mutation; Neural Stem Cells; Neurogenesis; Optic Lobe, Nonmammalian; Spindle Apparatus; Zebrafish